SERUM IRISIN AND LEPTIN LEVELS IN OBESE AND NON-OBESE WOMEN WITH POLYCYSTIC OVARY SYNDROME WITH REFERENCE TO GLUCOSE HOMEOSTASIS - Ali, Shatha H.; Al-nuaimi, Ali M. A.; Al-musawi, Bushra J. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: This study was aimed to evaluate the effect of serum leptin level on irisin level in relation to glucose homeostasis that to be associated with hormonal changes (Luteinizing hormone (LH), Follicle-stimulating hormone (FSH), Prolactin (PRL), Testosterone (TES)) in obese and non-obese women with polycystic ovary syndrome (PCOS). Methods: Fifty women with polycystic ovaries syndrome (PCOS) and thirty-four apparently healthy control women with regular menstruation (28±2days) were included in this study both of PCOS patients and controls were divided into sub-groups according to their body mass index (BMI) into: twenty-five obese (BMI ≥30) with (BMI= 35.934±0.746) and another twenty-five non-obese polycystic ovaries syndrome women (BMI=25.074±0.456). Whereas, controls were divided as seventeen obese (BMI= 37.140±1.470) and seventeen non-obese (BMI= 25.022±0.683) healthy control women with regular menstruation with an age range (20-40 y) and BMI matching that of the patient groups. Venous blood samples were collected to measure serum levels of luteinizing hormone (LH), follicle stimulating hormone (FSH), LH/FSH, prolactin (PRL), total testosterone (TES), thyroid stimulating hormone (TSH). As well as, fasting glucose, irisin, leptin, and insulin. Besides, estimating Insulin Resistance (HOMA-IR) index, β-cell function was determined using the Homeostasis Model Assessment of β-cell function (HOMA-β). Results: Serum irisin levels were not significantly different from their corresponding controls, in both obese and non-obese PCOS patients. Whereas, serum irisin levels were elevated significantly in both obese (patients and control) as compared to non-obese (patients and controls), respectively. But, serum leptin levels were significantly elevated in obese PCOS patients as compared to their corresponding control group, non-obese control, and non-obese PCOS patients. However, serum leptin levels were not significantly different in non-obese women groups, both the PCOS and controls. The irisin/insulin ratio expressed no significant variations from its corresponding control in non-obese groups. But the obese PCOS patient's values were highly significantly different as compared to their control (p<0.01). Furthermore, irisin/insulin ratio was elevated significantly in obese control as compared to non-obese patients (p = 0.001), but not with non-obese controls (p=0.114). The leptin/insulin ratio was not significantly varied in PCOS groups from their corresponding control in non-obese (p = 0.094) but in obese PCOS patients, there was significantly different as compared to its control (p = 0.01). Furthermore, leptin to insulin ratio was not significantly different between patients groups (non-obese and obese, p=0.133), nor between the studied controls (p=0.705). Conclusion: Although serum irisin levels show no significant variation in subjects in relation to PCOS condition, it seems more to be related to BMI, since it's secreted by adipocytes. And because leptin and irisin levels would be elevated in obese subjects that would be related to PCOS pathogenesis. However, irisin/leptin ratio could aid only in the differentiation of patients with PCOS and normal subjects within the same BMI values. Irisin/insulin ratio seems to be a better indicator for PCOS condition regardless to BMI, where it showed significantly lowered values and to be negatively correlated with HOMA-IR in obese and non-obese, and even to be significantly correlated with LH/FSH ratio in obese PCOS patients.